1976
DOI: 10.1104/pp.57.5.802
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-limited Growth Kinetics of Tobacco (Nicotiana rustica L.) Callus

Abstract: Logistic curves were fitted to sigmoidal growth data obtained from tobacco (Nicotiana rustica L.) callus grown on media prepared with 0.1, 0.03, 0.01, and 0.003 M sucrose. Analysis of the growth curves indicated that final yields and specific growth rates were influenced by the initial sucrose concentration. Growth yields from the four treatments were similar (0. MATERIALS AND METHODSTobacco callus cultures grown on Linsmaier and Skoog's medium (10) were used following preliminary tests with a large number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Uptake of solutes includes passive permeation of solute through the membrane, ‘solvent drag’ by the mass flow of the water, and active transport. The active and/or facilitated transport makes an important contribution to the uptake of dry materials by fruits, as studied in tomato (Milner, Ho & Hall 1995), in peach (Vizzotto et al 1996) and in tobacco callus (Hunt & Loomis 1976). Influx of water and solutes into the cells leads to irreversible changes in the volume if it is accompanied by cell wall extension.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of solutes includes passive permeation of solute through the membrane, ‘solvent drag’ by the mass flow of the water, and active transport. The active and/or facilitated transport makes an important contribution to the uptake of dry materials by fruits, as studied in tomato (Milner, Ho & Hall 1995), in peach (Vizzotto et al 1996) and in tobacco callus (Hunt & Loomis 1976). Influx of water and solutes into the cells leads to irreversible changes in the volume if it is accompanied by cell wall extension.…”
Section: Introductionmentioning
confidence: 99%
“…Growth, as measured by dry weight accumulation, can be strongly determined by the kinetics of synthetic reactions. Hunt and Loomis (13) demonstrated the relationship of tobacco callus growth to external sucrose concentration. Their results described a rectangular hyperbola with a Km of 3.7 mm.…”
Section: Hampson Loomis and Rainsmentioning
confidence: 99%
“…For the whole plant, there is considerable evidence that the most limiting factor to assimilate availability is assimilate production rather than vascular transport capacity. Investigation of the substrate dependence of growth rate in callus by Hunt and Loomis (13) suggested that the movement of assimilates within the sink tissue is also important.…”
mentioning
confidence: 99%
“…root, stem and leaf biomass are being constantly renewed). For the sake of simplicity and because we want to focus on the plant–insect interaction, we describe vegetative growth using a logistic growth rate, a choice that is empirically justified for tobacco plants [ 18 ]. In the absence of the plant, however, the insect always goes extinct because larval development relies exclusively on herbivory, even if adults pollinate other plant species.…”
Section: Methodsmentioning
confidence: 99%